Ultrasound contrast agent loaded with nitric oxide as a theranostic microdevice - Grishenkov D; Gonon A; Weitzberg E; Lundberg JO; Harmark J; Cerroni B; Paradossi G; Janerot-Sjoberg B (Dove Medical Press, 2015)
Dmitry Grishenkov,1–3 Adrian Gonon,3,4 Eddie Weitzberg,5 Jon O Lundberg,5 Johan Harmark,6 Barbara Cerroni,7 Gaio Paradossi,7 Birgitta Janerot-Sjoberg1–3 1Department of Clinical Science, Intervention, and Technology, Karolinska Institutet, Stockholm, Sweden; 2Department of Medical Engineering, KTH, Royal Institute of Technology, School of Technology and Health, Stockholm, Sweden; 3Department of Clinical Physiology, Karolinska University Hospital, Stockholm, Sweden; 4Department of Medicine, Karolinska Institutet, Stockholm, Sweden; 5Department of Physiology and Pharmacology, Karolinska Institutet, Stockholm, Sweden; 6Department of Biosciences and Nutrition, Karolinska Institutet, KTH, Royal Institute of Technology, School of Technology and Health, Stockholm, Sweden; 7Department of Chemical Sciences and Technologies, University of Rome Tor Vergata, Rome, Italy Abstract: The current study describes novel multifunctional polymer-shelled microbubbles (MBs) loaded with nitric oxide (NO) for integrated therapeutic and diagnostic applications (ie, theranostics) of myocardial ischemia. We used gas-filled MBs with an average diameter of 4 µm stabilized by a biocompatible shell of polyvinyl alcohol. In vitro acoustic tests showed sufficient enhancement of the backscattered power (20 dB) acquired from the MBs’ suspension. The values of attenuation coefficient (0.8 dB/cm MHz) and phase velocities (1,517 m/s) were comparable with those reported for the soft tissue. Moreover, polymer MBs demonstrate increased stability compared with clinically approved contrast agents with a fracture threshold of about 900 kPa. In vitro chemiluminescence measurements demonstrated that dry powder of NO-loaded MBs releases its gas content in about 2 hours following an exponential decay profile with an exponential time constant equal to 36 minutes. The application of high-power ultrasound pulse (mechanical index =1.2) on the MBs resuspended in saline decreases the exponential time constant from 55 to 4 minutes in air-saturated solution and from 17 to 10 minutes in degassed solution. Thus, ultrasound-triggered release of NO is achieved. Cytotoxicity tests indicate that phagocytosis of the MBs by macrophages starts within 6–8 hours. This is a suitable time for initial diagnostics, treatment, and monitoring of the therapeutic effect using a single injection of the proposed multifunctional MBs. Keywords: microbubbles, contrast agent, ultrasound, nitric oxide, myocardial ischemia